Cienciometria dos estudos genéticos em feijão-comum (Phaseolus vulgaris L.) - AMURIM, Ana Paula Viana (2024)
The common bean (Phaseolus vulgares L.) is a legume of great economic importance, being considered a rich and low-cost nutritional source. For this reason, it is the main dish on the table of the poorest populations, in addition to standing out as a source of employment and income, especially on small rural properties that practice family farming. Despite this, a large reduction in the production and consumption of common beans has been noticed, mainly due to environmental problems that affect production yield, causing uncertainty in relation to harvest yield. In addition, there is also a decrease in consumption due to the increase in prices related to high inflation in recent years, which increases the prices of the main items that make up Brazilians' basic food basket, such as beans. Genetic improvement studies have contributed to the development of cultivars that enable increased productivity, resistance to pests and climatic factors, aiming to minimize losses and sustainable grain production, reducing negative factors such as the impacts caused by artificial fertilization and incorrect soil management. Scientometrics seeks to analyze, through quantitative data, the scientific production of a given topic of study to map the evolution or decline of fields of science, in addition to identifying emerging areas that require greater financial support or human resources to better progress. This contributes to directing studies towards areas of real relevance. Based on this, this project aimed to evaluate the scientific production regarding genetic studies in common beans through a scientometric analysis methodology with a view to defining the main areas and subareas of knowledge covered by the published articles; relate the techniques used to analyze genetic aspects and propose guidance strategies for future studies on the species.